Air Contamination in Operating Theatres: The Key Factors That Can Influence It - Lorenzo Dragoni; Davide Amodeo; Gabriele Cevenini; Nicola Nante; Maria Francesca De Marco; Gabriele Messina (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: Continuous monitoring of airflows, correlated with door opening and closing and the number of operators, can help predict levels of microbiological air contamination and thus prevent surgical infections.